Analisis Data Curah Hujan yang Hilang Dengan Menggunakan Metode Normal Ratio, Inversed Square Distance, dan Cara Rata-Rata Aljabar (Studi Kasus Curah Hujan Beberapa Stasiun Hujan Daerah Bandar Lampung) - Prawaka, Fanny; Zakaria, Ahmad; Tugiono, Subuh (Universitas Lampung, 2016)
This research is done with the purpose to calculate the correlation of measurable rainfall data with rainfall data on the calculation using each method mentioned above which is every method using three rainfall stasions, four rainfall stasions, and five rainfall stasions. It’s also purposed to decide with how many stasions and what method is resulting the best correlation value. As the result of the research using algebraic average method, normal ratio method, and inversed square distance method with daily rainfall data in a year, cumulative monthly rainfall data, and also average monthly rainfall data, it can be concluded that the greater number of stasions resulting the better correlation value. The correlation value with cumulative monthly rainfall data and average monthly rainfall data using some different number of stasions for each method is resulting a not significant differences with the value of percentage is 0,00025% to 0,01182%. Thecalculation uses cumulative monthly rainfall data and average monthly rainfall data showing the better correlation value than calculation using daily rainfall data in a year (0,67230 - 0,72097compared to 0,19305 - 0,25890). Keywords: Rainfall, normal ratio method, inversed square distance method, algebraic average method